Representation of the Solution for Fractional Sturm-Liouville Problem - Bas, Erdal; Metin, Funda (Amer Inst Physics, 2016)
In this paper, the representation of solution for the fractional Sturm-Liouville problem is obtained by modified method of variation of parameters. It is shown that this method is applicable for fractional differential equations.
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 23-29, 2015 -- Rhodes, GREECE